Using an academic-community partnership model to deliver evidence-based falls prevention programs in a metropolitan setting: A community case study - Elrod, Cathy S.; Pappa, Sara T.; Heyn, Patricia C.; Wong, Rita A. (Frontiers in Public Health, 2023)
Background Prevention is an effective approach for mitigating the negative health outcomes associated with falls in older adults. The Administration for Community Living (ACL) has sponsored the implementation of evidence-based falls prevention programs (EBFPPs) across the United States through cooperative agreement grants to decrease the health and economic burden of falls. Marymount University received two of these grants to deliver three EBFPPs into the northern Virginia region. This community case study describes the development of a collaboration between a university and community-based organizations to adopt and implement multiple evidence-based programming in an area where none previously existed. Methods Through an academic-community partnership, EBFPPs were introduced to and implemented by senior-focused organizations. Target adopters were senior and community centers, multi-purpose senior services organizations, recreational organizations, and residential facilities serving older adults. The three EBFPPs were (1) Stay Active and Independent for Life (SAIL), (2) a Matter of Balance (MOB) and (3) Otago Exercise Program (OEP). Key interdependent project elements included: (1) fostering ongoing community organization collaboration, (2) introducing programs in the community, (3) growing and sustaining delivery sites, (4) preparing trained program leaders, and (5) building community demand for the programs. Results From August 2016–June 2022, 5,857 older adults participated in one of the three EBFPPs. SAIL classes were offered at 33 sites and MOB workshops at 31 with over 70% of them occurring at community or senior centers. OEP was offered at 4 sites. Factors that influenced the implementation of these programs included having: key advocates at host organizations, programs embedded into site workflows, sufficient capacity and workforce, engaged invested partners, and flexibility in working with a complex set of agencies and systems with different administrative structures. Conclusion By connecting academic faculty with various community members from multiple sectors, new initiatives can be successfully implemented. Results from this ACL-funded project indicate that using an academic-community partnership model to build relationships and capacity for ongoing delivery of health promotion programming for older adults is feasible and effective in delivering EBFPPs. In addition, academic-community partnerships can develop a strong network of invested partners to foster continued support of fall prevention activities.